ASSESSMENT OF THE EFFECT OF PUSHBACK Z-PLASTY METHOD ON THE FUNCTION OF VELOPHARYNGEAL AND ARTICULATION IN POST-RECONSTRUCTION CLEFT PALATE PATIENTS IN HARAPAN KITA CHILDREN AND MATERNITY HOSPITAL JAKARTA: PENILAIAN PENGARUH Z-PLASTY PADA METODA PUSHBACK TERHADAP FUNGSI VELOPHARYNGEAL DAN FUNGSI ARTIKULASI PADA PENDERITA PASCA REKONSTRUKSI CELAH LANGIT-LANGIT DI RSAB HARAPAN KITA JAKARTA - Hanafiah, Olivia Avriyanti; Manullang, Kasman; Firman, Mantra; Hak, Muhammad Syafrudin (Dentika: Dental Journal, 2017)
Cleft palate patients experience various problems, especially those affecting their speech intelligibility, such as speech articulation disorder. The aim of this research was to prove the effect of cleft palate reconstruction with modified pushback z–plasty technique at the nasal mucosa on velopharyngeal function and articulation function in speaking. A research has been conducted on post-reconstruction cleft palate patients by using modified pushback z-plasty technique at the nasal mucosa. The methods were examining velopharyngeal components with cephalometric radiograph, assessing airflow released from the nose when the patients pronounce vowel ‘a’ using nasal emission device and assessing speech articulation results through Sehati Program at Harapan Kita Children and Maternity Hospital, Jakarta. The research results showed that there was a statistically significant effect of cleft palate reconstruction with pushback z-plasty technique at the nasal mucosa on velopharyngeal function, and there was a statistically significant effect of cleft palate reconstruction with pushback z-plasty technique at the nasal mucosa on articulation function in speaking. In addition, there was also a statistically significant correlation between velopharyngeal function and speech articulation function of post-reconstruction cleft palate patients with pushback z-plasty technique at the nasal mucosa based on the cephalometric radiograph, but the result was not significant statistically based on nasal emission assessment.